“Where I’m Coming From”: A Discourse Analysis of Financial Advice Media - Tanya E Mudry; Ines Sametband; Tom Strong; Dan Wulff; Jennifer Michel; Sally St. George (Journal of Financial Therapy, 2014)
In this paper we conceptualize different understandings and positions taken in conflicts over finances in family and couple relationships. We see these as informed by discourses found in popular and professional media. Discourses, as we describe them, are cultural ways of understanding and acting – where “we are coming from,” in this case, relates to finances and financial management. We turn to various media (magazine advice articles, self-help books, professional and research literatures) using discourse analysis to identify distinct discourses regarding how finances are to be regarded and managed. We then link these discourses to discourse positions, or positionings, that partners and family members present that could be relevant to concerns about finances presented to relational therapists and financial therapists. We offer questions and other ways of avoiding “capture” in discourse positions that can be harmful to relationships, including the therapeutic relationship.
Keywords: discourse analysis; financial therapy; families and couples; media; self-help